El incumplimiento y la falta de Políticas Públicas para la Reinserción Laboral de las personas que han cumplido una Pena Privativa de Libertad - Tenemea Cuenca, Karen Vanessa (2023)
The present curricular integration work, entitled "The non-compliance and the lack of Public Policies for the Labor Reintegration of people who have served a custodial sentence", is of great interest to develop its research because the country faces severe insecurity in society and a great increase in delinquency due to the fact that within the Penitentiary Centers, there is no correct rehabilitation, as well as the lack of job opportunities for people who have served a sentence. We are facing a social problem for which the State is responsible, since its highest duty consists of respecting and enforcing the rights guaranteed in the Constitution, as well as being responsible for actions or omissions in the face of violation, non-compliance and impairment. of these rights enshrined both in the Constitution and in the international instruments signed by the Ecuadorian State. In the present investigation, the main objective has been "to determine the lack of employment contracts for people who have served a custodial sentence, to implement post-prison support programs", within the Constitution of the Republic of Ecuador mentions that all people are equal and enjoy the same rights, duties and opportunities, and recognizes that work is a right and a social duty, a source of personal fulfillment and the basis of the economy, it also mentions that the Social Rehabilitation System has the purpose of rehabilitate the prisoner to fully reintegrate into society, however, within this research, through the materials and methods used such as interviews, surveys of professionals knowledgeable about the subject, it has been determined that people who have served a custodial sentence do not get a job, it is due to several factors among them, that there is a deficit of sources of employment, the di discrimination and social stigmas and the strongest fear that employers have when hiring these people since they consider that they have not received a correct rehabilitation so they could return to offending.